2020
DOI: 10.3906/sag-1910-69
|View full text |Cite
|
Sign up to set email alerts
|

Which Bayley-III cut-off values should be used in different developmental levels?

Abstract: Introduction Bayley Scales of Infant and Toddler Development 2nd Edition (BSID-II) and its latest version Bayley Scales of Infant and Toddler Development 3rd Edition (Bayley-III) are currently the most widely used standardized developmental tools in both clinical practice and research settings for assessment of development in infancy and early childhood (0-42 monhts), early diagnosis of developmental delays, providing information for early intervention planning, and assessment of the efficiency of these interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…However, there are concerns over the standardization of the Bayley-III and the use of US norms in different countries, given widespread cross-cultural evidence for the overestimation of cognitive function using Bayley-III norms. [15][16][17][18][19][20][21] The present study followed the recommendation of using a cut-off for mild cognitive delay of less than 1 SD below the mean of a geographically relevant control group, to improve the detection of developmental delay. 15,22 Previous researchers reported this cut-off to fall around 90, based on a mean cognitive composite score of approximately 105 and an SD of 15.…”
Section: Instrumentsmentioning
confidence: 99%
“…However, there are concerns over the standardization of the Bayley-III and the use of US norms in different countries, given widespread cross-cultural evidence for the overestimation of cognitive function using Bayley-III norms. [15][16][17][18][19][20][21] The present study followed the recommendation of using a cut-off for mild cognitive delay of less than 1 SD below the mean of a geographically relevant control group, to improve the detection of developmental delay. 15,22 Previous researchers reported this cut-off to fall around 90, based on a mean cognitive composite score of approximately 105 and an SD of 15.…”
Section: Instrumentsmentioning
confidence: 99%
“…As an example, those exposed to PM 10 levels at the 75 th percentile (32.50 µg/m 3 ) compared to the 25 th percentile (26.64 µg/m 3 ) of exposure were predicted to have a three point lower composite cognitive score. For context, in the current study, 16% of participants had a composite cognitive score that indicated some degree of impairment [ 40 , 41 ]. If all participants had PM 10 levels at the 75 th percentile of exposure, the prevalence of cognitive impairment would be predicted to increase to 22%, which highlights the importance of even moderate increases in early-life exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Second, neurodevelopmental assessment was performed at six months CA, which might be too early to capture the subtle cognitive, language, and motor development differences. Results of the standardised tests showed very little variability, with the vast majority of children having scores considered as normal [ 20 , 21 ]. Additionally, Nordhov et al showed better cognitive performance at five years of age after being exposed to the MITP in the neonatal period [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main outcome of this study concerned the six-month CA neurodevelopment of the preterm neonates, which was evaluated by the Bayley Scales of Infant and Toddler Development, 3rd Edition (BSID-III) [ 19 , 20 , 21 ]. This standardised test examines three domains of development: cognition, language (receptive and expressive communication), and motor skills (fine and gross motor).…”
Section: Methodsmentioning
confidence: 99%